A pandemia da COVID-19 e a Odontologia: implicações para a clínica, para o ensino-aprendizagem e para a extensão - Carvalho, Thiago de Amorim (2021)
The pandemic of COVID-19 brought up discussions about processes of use of digital tools for higher education, never seen before. Thus, it is necessary and urgent to reflect and, especially, to deepen studies on the impacts of this pandemic in the teaching-learning processes, in university extension, and in the dental clinic itself. The ubiquitous and mobile learning modalities have become a reality for the maintenance of the teaching-learning processes, with emphasis on Instagram as the digital tool used in this study. It was noticed that the content of Instagram pages are often permeated by posts of personal nature, and despite the large number of followers of dentistry pages this content still lacks greater scientific evidence. Regarding the use of Instagram by dental students from public and private institutions, the results show that income is not a limiting factor for access, although the presence of reliable references in the content guides the search for content on dental pages of the social network. The maintenance of the extension activities was possible because of synchronous and asynchronous remote tools, whether for the development of educational material aimed at the population, in the form of booklets and transforming them into audiovisual media to make them more comprehensive and accessible, using different applications, or for the maintenance of synchronous educational processes in health, even for populations deprived of freedom, in social vulnerability, such as adolescent offenders. The health information could reach places that perhaps in other contexts, given the geographical limits, but especially the social ones and those related to prejudice would not reach. Still in the dental clinic, knowledge had to be acquired concerning the learning of oral manifestations of COVID-19, a new disease with a pathogenesis still barely elucidated. The mouth seems to be a site of manifestations that can either direct the diagnosis or indicate a darker prognosis for patients affected by this condition. Oral ulcers, candidosis, and dysgeusia seem to be common in people infected by the coronavirus, and their identification is necessary, given the perennial circulation of this etiologic agent among the population and the training of professionals involved with the social reality. It can be stated that the COVID-19 pandemic brought with it several impacts on dental training, many of which raise important reflections on the educational processes in the scope of higher education and of teaching and clinical professional updating.